The Jurisprudence of Protection: A Comparative Analysis of Istiʿādhah in the Fatwas of Ibn Bāz and al-‘Uthaymīn - Luqman; Agung Pranoto Kadiatmaja (Jurnal Hadratul Madaniyah, 2026)
The discourse on istiʿādhah (seeking protection) remains particularly relevant in contemporary contexts where practices of spiritual protection, such as ruqyah, tawassul, and popular spiritualism, risk blurring the boundaries between tawḥīd (monotheism) and shirk (polytheism). This study aims to analyze the concept of istiʿādhah as addressed in the fatwas of ʿAbd al-ʿAzīz ibn Bāz and Muḥammad ibn Ṣāliḥ al-ʿUthaymīn, highlighting both convergences and divergences in their theological reasoning. The research utilizes a qualitative-comparative approach, employing library research and thematic content analysis, alongside the constant comparative method to examine primary fatwa sources. The findings reveal that both 'ulama agree on istiʿādhah as an essential element of tawḥīd al-ulūhiyyah (the oneness of Allah), which must be directed exclusively to Allah. However, their istinbāṭ (legal reasoning) differs: Ibn Bāz applies a deductive-practical approach focused on ritual guidance, while al-ʿUthaymīn uses an inductive-systematic method that emphasizes theological classification. The primary contribution of this research lies in the reconstruction of the "Jurisprudence of Protection," a novel conceptual framework that systematically classifies istiʿādhah into three categories: sharʿiyyah (prescribed), jāʾizah (permissible), and shirkīyyah (polytheistic). This framework provides crucial theological navigation for fatwa authorities and the Muslim community, helping them distinguish between legitimate spiritual protection practices, those permissible in limited circumstances, and those that deviate from the core principles of tawḥīd in contemporary religious practices.